Carrier-Induced Hyporesponsiveness to Pneumococcal Conjugate Vaccines: Unraveling the Influence of Serotypes, Timing, and Previous Vaccine Dose. (29th January 2020) - Dagan, Ron; Jiang, Qin; Juergens, Christine; Trammel, James; Gruber, William C; Scott, Daniel A
Abstract: Background: Pneumococcal conjugate vaccines (PCVs) elicit lower immune response against serotypes carried before or at the time of vaccination (hyporesponsiveness) in infants. The limited studies conducted to date did not permit comprehensive insights regarding this phenomenon. This study, the largest ever conducted with both carriage and serologic endpoints, attempted to add insight on serotype-specific hyporesponsiveness in relation to the number of PCV doses administered before carriage acquisition. Methods: In a double-blind randomized clinical trial (n = 1754 infants), 7-valent or 13-valent PCV was administered at ages 2, 4, 6, and 12 months. New acquisition was defined based on nasopharyngeal swabs at ages 2, 4, 6, 7, and 12 months. Serotype-specific immunoglobulin G levels were obtained 1 month after the infant series and 1 month after the toddler dose. Results: A lower immune response after the infant series and the toddler dose was consistently observed for carriers of serotypes 6A, 6B, 18C, and 19F at predefined time points, with a similar trend observed in carriers of serotype 23F. In contrast, carriage of serotypes 9V, 14, and 19A did not generally affect immune responses. For some but not all serotypes, hyporesponsiveness was decreased with an increased number of vaccine doses received before acquisition. A complex interrelationship between carriage and immune response was observed between cross-reacting serotypes. Conclusions: Carrier-induced hyporesponsiveness to PCVs is common, differs among serotypes, and depends on timing of carriage acquisition and prior number of administered PCV doses. Clinical Trials Registration: NCT00508742. Abstract : Serotype-specific hyporesponsiveness of serological response to pneumococcal conjugate vaccines following acquisition of commonly carried pneumococcal serotypes in infants is complex and dependent on serotype and number of previous vaccine doses. This analysis showed no hyporesponsiveness following carriage of cross-reacting serotypes.